2015
DOI: 10.1007/s00705-015-2521-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensin II in experimental Venezuelan equine encephalitis in rats

Abstract: Venezuelan equine encephalitis (VEE) is a viral disease transmitted by mosquitoes. The inflammation induced by the VEE virus is associated with a high mortality rate in mice. Angiotensin II (Ang II), a pro-inflammatory molecule, is produced in the normal rat brain. There is no information about the role of this molecule in the inflammatory events occurring during VEE and the effect of inflammation on the mortality rate in VEE-virus-infected rats. This study was designed to determine the role of Ang II in VEE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…These investigators found that Ang II expression increased rapidly in the CNS following VEEV infection, but that daily treatment of animals with losartan (30 mg/kg) actually accelerated death compared to rats given a vehicle control [60]. In their hands, losartan suppressed VEEV-mediated induction of the pro-inflammatory mediators, IL-1α and CCL2, as well as the anti-inflammatory compound, IL-10, but had no effect on IL-6 levels in the brain [60]. Drug treatment also reduced vascular pathology in the CNS of VEEV-infected animals, but had no quantitative effects on cellular infiltration into the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These investigators found that Ang II expression increased rapidly in the CNS following VEEV infection, but that daily treatment of animals with losartan (30 mg/kg) actually accelerated death compared to rats given a vehicle control [60]. In their hands, losartan suppressed VEEV-mediated induction of the pro-inflammatory mediators, IL-1α and CCL2, as well as the anti-inflammatory compound, IL-10, but had no effect on IL-6 levels in the brain [60]. Drug treatment also reduced vascular pathology in the CNS of VEEV-infected animals, but had no quantitative effects on cellular infiltration into the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Drug treatment also reduced vascular pathology in the CNS of VEEV-infected animals, but had no quantitative effects on cellular infiltration into the brain. They concluded that Ang II-driven neuroinflammation could be a host defense mechanism that limits virus damage and favors survival [60]. Unfortunately, however, their conclusions contradict numerous other studies showing that host responses actually drive VEEV pathogenesis and directly contribute to mortality [6163].…”
Section: Discussionmentioning
confidence: 99%